TRI PUSAT PENDIDIKAN (KELUARGA, SEKOLAH, DAN MASYARAKAT) DALAM MEMBENTUK AKHLAK MELALUI PEMBINAAN AGAMA - Lili Hastuti (Pusat Studi Pendidikan dan Kreatifitas Anak Purwokerto, 2020)
Education as a process that certainly cannot be separated from social life. Social life in the sphere of education is the Tri Education Center which includes families, schools, and communities. The family as the starting place for education, the school as the second place after the family, and finally students are able to adjust to the community environment according to the directions obtained from the family and school environment which is supported by fostering religious activities. The three of them must work together in order to achieve educational goals. The core of the purpose of education, especially Islamic education is in order to form good morals to students by integrating affective, cognitive, and psychomotor aspects. The three central points of education must be integrated even though the most important is from the family. Good collaboration between the three will be able to create students according to the digital age while still promoting moral or moral. In essence, if the three work well together and are supported by high motivation from students, students will create morals according to the digital era without releasing the nature of morals.